Evaluating the User Experience of a Mobile Ticketing Application using the User Experience Questionnaire (UEQ) - Bailaen, Elsa Anjamilen; Bangkalang, Dwi Hosanna (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The digitalization of the mobile ticketing sector in Indonesia has seen significant growth, with a projected 50% increase in mobile ticketing app usage by 2025. Popular applications such as Traveloka, Tiket.com, Agoda, and Booking.com dominate the market, yet they face several technical challenges, including navigation difficulties, unclear interfaces, performance bugs during peak hours, slow application response times, and limited features. This study employed the User Experience Questionnaire (UEQ) method and involved 578 respondents selected through purposive sampling. The criteria included active users of one of the mobile ticketing apps and individuals aged between 20 and 40 years. The results of the t-test revealed that Agoda needs to improve the perspicuity aspect by simplifying its dense user interface, particularly in accommodation and travel ticket searches. Regarding efficiency, Traveloka, Agoda, and Booking.com must enhance their search systems and address bugs/errors that disrupt performance during peak usage times. For stimulation, Traveloka should enhance user experience by providing a more dynamic and responsive layout when navigating pages or performing searches. In terms of novelty, both Agoda and Booking.com are advised to integrate local e-wallets such as GoPay, OVO, and DANA, as well as bank transfer options, since currently they only support credit card payments. These findings highlight the critical role of UX in improving user satisfaction and suggest that continuous user-centered development is essential for maintaining competitiveness in the mobile ticketing industry.